THE EFFECT OF PRODUCT INNOVATION, ENDORSEMENTS AND REPUTATION RELATION WITH BRAND IMAGE AND BRAND AWARENESS TOWARD AFFIRMATIVE OF PURCHASE DECISION - Ida Bagus Nyoman Udayana (Journal of Management and Business, 2015)
The purpose of this paper is to understand the effect of product innovation, endorsements and brand image related to brand awareness and reputation for affirmative purchasing decisions on Solo Medicinal Products Fountain. Data were collected using random sampling. Sample size is 200, and 165 questionnaires were returned. The results showed that product innovation and reputation and a significant positive effect on brand image, reputation and endorsement and significant positive effect on brand awareness, brand image and brand awareness positivelyeffect to purchase intentions, purchase intentions positive and significant effect on the stability of the purchasing decision.Findings: The updates of this research are the research model in terms of purchase intention is then forwarded to the stability variable purchase decision. Usually during this study only stop on purchase intentions on steadiness or stop buying decision but did not begin with the intention ofbuying. Though stability begins with the decision to buy should purchase intention.